PERAN MASYARAKAT DALAM MENJAGA KEBERSIHAN LINGKUNGAN DESA MEDANKARYA - Harianja, Rafael Divio; Aditya, Indra; Azijah, Dewi Noor (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2025)
This study examines the participation of the Medankarya Village community in supporting local socioeconomic conditions using an exploratory qualitative approach. The entire village population was included in the study, with interviews, observations, documentation, and field notes serving as data collection instruments. The results indicate that there are no waste management facilities in the village or sub-district, and some residents remain unconcerned about environmental cleanliness. However, the village government has developed several environmental management programs, emphasizing the importance of a Waste Processing Facility for the village.